United States : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
The U.S. economy continues to recover at a modest pace, in line with international experience following severe financial crises. The key priority for fiscal policy is to stabilize the debt ratio and gradually reduce it. The fiscal framework should include an endorsement of the main medium-term fiscal objectives. Executive Directors recommend policy efforts to ease the adjustment of the housing and labor markets. Strengthening the domestic and international crisis-prevention architecture for financial institutions should be a priority. A multilateral approach to economic policy management is critical.